HUKUM EKONOMI ISLAM DI INDONESIA PADA ZAMAN KEMERDEKAAN - Ikhwan Matondang, Joni Zulhendra, Asasriwarni dan (Normative Jurnal Ilmiah Hukum, 2021)
Islamic economics in legal regulations in Indonesia is contained in the Elucidation of Law of the Republic of Indonesia Number 50 of 2009 concerning Amendments to Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning Religious Courts Letter I What is meant by "sharia economy" ahâ€ is an act or business activity that is carried out according to the principles of Shari'ah. This article discusses how the development of Islamic economic law during the independence period. The method used in this study the author uses normative research procedures, where by looking at the law as a rule. In obtaining information using library research procedures, the method is to study legal literature related to the subject matter, a collection of statutory regulations, legal posts and various other written sources. The conclusion of this study, in the early days of independence, Indonesia's economic condition was in a bad situation. Factors that caused the poor economic condition of Indonesia at that time, among others, the occurrence of very high inflation caused by the circulation of too much money. The next development is the existence of sharia economic regulations which are legal products that regulate sharia financial institutions that have been issued, namely Law Number 7 of 1992 concerning Banking and Law Number 10 of 1998 concerning Banking, Law Number 38 of 1999 concerning Zakat Management , Law Number 3 of 2006 concerning Religious Courts, Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 21 of 2008 concerning Sharia Banking, Law Number 33 of 2014 concerning Guaranteed Halal Products (JPH) and Law No. Law Number 40 of 2014 concerning Insurance.